2017
DOI: 10.1186/s12964-017-0187-9
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of TRPM7 suppresses cell proliferation of colon adenocarcinoma in vitro and induces hypomagnesemia in vivo without affecting azoxymethane-induced early colon cancer in mice

Abstract: BackgroundMagnesium (Mg2+) is an essential cation implicated in carcinogenesis, solid tumor progression and metastatic potential. The Transient Receptor Potential Melastatin Member 7 (TRPM7) is a divalent ion channel involved in cellular and systemic Mg2+ homeostasis. Abnormal expression of TRPM7 is found in numerous cancers, including colon, implicating TRPM7 in this process.MethodsTo establish a possible link between systemic magnesium (Mg2+) status, the Mg2+ conducting channel TRPM7 in colon epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 35 publications
(66 reference statements)
0
16
0
Order By: Relevance
“…The properties of TRPM7 as the channel and kinase and compensatory maintenance of Mg 2+ homeostasis causes the difficulties for revealing the roles of Mg 2+ in animal developments. Recently, some groups have shown that inactivation of the TRPM7 channel in living mice results in impaired Mg 2+ transport, supporting the notion that the TRPM7 channel indeed can function as important Mg 2+ channel in vivo [165,169]. Moreover, careful analysis using TRPM7 mutants lacking kinase domain support that TRPM7-mediated Mg 2+ influx is essential for embryonic developments in vertebrate [10,170].…”
Section: Effects Of Mg2+ On the Cellular Fate And Phenotypementioning
confidence: 92%
“…The properties of TRPM7 as the channel and kinase and compensatory maintenance of Mg 2+ homeostasis causes the difficulties for revealing the roles of Mg 2+ in animal developments. Recently, some groups have shown that inactivation of the TRPM7 channel in living mice results in impaired Mg 2+ transport, supporting the notion that the TRPM7 channel indeed can function as important Mg 2+ channel in vivo [165,169]. Moreover, careful analysis using TRPM7 mutants lacking kinase domain support that TRPM7-mediated Mg 2+ influx is essential for embryonic developments in vertebrate [10,170].…”
Section: Effects Of Mg2+ On the Cellular Fate And Phenotypementioning
confidence: 92%
“…Administration of NS8593 in vivo could lead to perturbances in the systemic divalent cation homeostasis due to suppression of TRPM7-dependent uptake of minerals in the colon, as has previously shown for waixenicin A, a natural product inhibitor of TRPM7 derived from Sarcothelia edmonsoni 35 . It will be interesting to see whether the protective effect of TRPM7 suppression in kidney fibrosis is mainly due to TRPM7 channel or kinase activity itself, a likely hypomagnesemia induction (or divalent perturbance), or a combination thereof.…”
Section: Discussionmentioning
confidence: 78%
“…One concern for this study is that there is no ideal specific TRPM7 inhibitor. We screened several TRPM7 inhibitors, 2-APB, Gin Rd, and Waix A, but none of these inhibitors are specific to TRPM7: (a) 2-APB affects inositol 1,4,5-trisphosphate receptors, store-operated calcium channels and TRP channels, TRPV3 and TRPM7 [16,27]; (b) Gin Rd affects TRPM channels, acid-sensing ion channels (ASIC), and some cation channels [17,28]; (c) Waix A is a newly identified TRPM7 inhibitor [29,30]. Although Waix A does not inhibit TRPM2, TRPM4, TRPM6 or CRAC channels, its potency depends on the intracellular Mg 2+ concentration and it is known to affect some cell lines that do not express TRPM7 [18,30].…”
Section: Discussionmentioning
confidence: 99%